Exploration Of Employee Experience In Maintaining Work-Life Balance In The Company - Maruf, Mahroza Sidqin Al; Ambarita, Novaldo Cristian; Alamsya, Gilang Damar; Permana, Aditya Agus; Fadillah, Mokhamad Farhan (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study aims to explore employees’ experiences in maintaining a balance between work and personal life (work-life balance) within corporate environments. Using a qualitative approach, data were collected through in-depth interviews with ten employees from various industrial sectors in Bandung. The results show that flexible working hours, managerial support, and a supportive organizational culture are key factors in achieving work-life balance. However, challenges such as high workloads and a lack of management’s understanding of employees’ personal needs remain significant obstacles. These findings imply that companies should design policies that are more responsive to employees' needs for balancing work and personal life.